Tafsir Hakim Judex Facti dan Judex Juris Terkait Batas Maksimal Upaya Administratif - Said, Muhtar; Erfandi, Erfandi (Fakultas Hukum Universitas Bangka Belitung, 2023)
To administrative effort in the form of an objection, a maximum time of 21 working days is given. However, there are differences in the application of these administrative efforts between judex facti judges and judex juris judges. Judex facti judges through decisions number 21/G/2020/PTUN and 76/B/2021/PT.TUN JKT implementing administrative measures are mandatory, this decision was upheld by judges at the State Administrative High Court. However, the decision was annulled by the judge judex juris (Supreme Court level) through decision number 420 K/TUN/2021. The basis for the judex juris to cancel the judex facti decision is based on the phrase